Analisis Optimalisasi, Transparansi dan Efisiensi Pengelolaan Dana Zakat Pada Badan Amil Zakat Nasional (Baznas) Sidoarjo - Achmad Yusuf; Masruchin Masruchin (Perisai : Islamic Banking and Finance Journal, 2021)
Zakat is one of the pillars of philanthropy in Islam. In its management, of course, must carried out and comply with applicable laws. There are several zakat institutions in Indonesia, One of them is the National Amil Zakat Agency (Baznas). This research aims to see the extent to which the level of optimization, transparency and efficiency of zakat management at the Amil Agency National Zakat (Baznas) in Sidoarjo. Data collection techniques used in This study uses observation and interviews. The results of this research discussion areoptimization can be said to be quite optimal by utilizing human resources in the inside and outside Baznas to drive distribution optimization levels. Transparency has not been said to be maximal because there is no financial reporting to the public overall. The management efficiency in 2019 was 128.9%.